2016
DOI: 10.1101/078766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining Multiscale Diffusion Kernels for Learning the Structural and Functional Brain Connectivity

Abstract: The activation of the brain at rest is thought to be at the core of cognitive functions. There have been many attempts at characterizing the functional connectivity at rest from the structure. Recent attempts with diffusion kernel models point to the possibility of a single diffusion kernel that can give a good estimate of the functional connectivity. But our empirical investigations revealed that the hypothesis of a single scale best-fitting kernel across subjects is not tenable. Further, our experiments demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, this model uses one global parameter across all the subjects, and the hypothesis of a single scale best-fitting kernel across subjects is not tenable. Surampudi et al [6] observed that the combination of multiple diffusion scales exhibits scale-dependent relationships among various regions of interest 115 (ROIs), and these multi-scale diffusion kernels can capture reaction-diffusion systems operating on a fixed underlying connectome (SC). However, multiple diffusion kernels were not sufficient to explain the self-organizing resting-state patterns found in FC.…”
Section: Graph-theoretic Modeling Using Linear Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this model uses one global parameter across all the subjects, and the hypothesis of a single scale best-fitting kernel across subjects is not tenable. Surampudi et al [6] observed that the combination of multiple diffusion scales exhibits scale-dependent relationships among various regions of interest 115 (ROIs), and these multi-scale diffusion kernels can capture reaction-diffusion systems operating on a fixed underlying connectome (SC). However, multiple diffusion kernels were not sufficient to explain the self-organizing resting-state patterns found in FC.…”
Section: Graph-theoretic Modeling Using Linear Modelsmentioning
confidence: 99%
“…Similarly, in [6], the mixing coefficients are subsequently learned while solving an optimization formulation as:…”
Section: Relation To Reaction Diffusion Phenomenonmentioning
confidence: 99%
See 3 more Smart Citations